I-PASS Mentored Implementation Handoff Curriculum: Champion Training Materials - Jennifer K. O'Toole; Amy J. Starmer; Sharon Calaman; Maria-Lucia Campos; Jennifer Hepps; Joseph O. Lopreiato; Shilpa J. Patel; Glenn Rosenbluth; Jeffrey L. Schnipper; Theodore C. Sectish; Rajendu Srivastava; Daniel C. West; et al. (Association of American Medical Colleges, 2019)
Introduction The I-PASS Handoff Program is a comprehensive handoff curriculum that has been shown to decrease rates of medical errors and adverse events during patient handoffs. I-PASS champions are a critical part of the implementation and sustainment of this curriculum, and therefore, a rigorous program to support their training is necessary. Methods The I-PASS Handoff champion training materials were created for the original I-PASS Study and adapted for the Society of Hospital Medicine (SHM) I-PASS Mentored Implementation Program. The adapted materials embrace a flipped classroom approach and adult learning theory. The training includes an overview of I-PASS handoff techniques, an opportunity to practice evaluating handoffs with the I-PASS observation tools using a handoff video vignette, and other key implementation principles. Results As part of the SHM I-PASS Mentored Implementation Program, 366 champions were trained at 32 sites across North America and participated in a total of 3,491 handoff observations. A total of 346 champions completed the I-PASS Champion Workshop evaluation form at the end of their training (response rate: 94.5%). After receiving the training, over 90% agreed/strongly agreed that it provided them with knowledge or skills critical to their patient care activities and that they were able to distinguish the difference between high- and poor-quality handoffs, competently use the I-PASS handoff assessment tools, and articulate the importance of handoff observations. Conclusion The I-PASS champion training materials were rated highly by those trained and are an integral part of a successful I-PASS Handoff Program implementation.